The Potential of Dosimetry and the Visualization of Microbeam Arrays in NIPAM Gel at the PETRA III Synchrotron - Breslin, Thomas; Kügele, Malin ; 0000-0002-7213-111X; de Rover, Vincent; Fiedler, Stefan; Lindner, Tobias; Klingenberg, Johannes; Faria, Guilherme Abreu; Frerker, Bernd; Nuesken, Frank; Ceberg, Sofie; Ceberg, Crister ; 0000-0003-1255-0336; Lerch, Michael; et al. (Gels, 2025)
Spatially fractionated radiotherapy (SFRT) is emerging as a powerful tool in cancer therapy for patients who are ineligible for treatment with clinically established irradiation techniques. Microbeam radiotherapy (MRT) is characterized by spatial dose fractionation in the micrometre range. This presents challenges in both treatment planning and dosimetry. While a dosimetry system with a spatial resolution of 10 µm and an option for real-time readout already exists, this system can only record dose in a very small volume. Thus, we are exploring dosimetry in an N-isopropylacrylamide (NIPAM) gel as an option for 3D dose visualization and, potentially, also three-dimensional dosimetry in larger volumes. In the current study, we have recorded the geometric patterns of single- and multiport irradiation with microbeam arrays in NIPAM gel. Data for 3D dose distribution was acquired in a 7T small animal MRI scanner. We found that the resolution of the gel is well suited for a detailed 3D visualization of microbeam patterns even in complex multiport geometries, similar to that of radiochromic film, which is well established for recording 2D dose distribution in MRT. The results suggest that a dose–response calibration is required for reliable quantitative dosimetry.
Publisher Copyright: © 2025 by the authors.
Keywords: 3D visualization; beam geometry; dosimetry; microbeam radiotherapy (MRT); MRI; NIPAM gel; spatially fractionated radiotherapy